Impact of Microfinance Grants on Rural Development: A case study of Kavango East Regional Council - Kavindja, Anna (Graduate School of Business (GSB), 2019)
This study looked at the impact of microfinance grants on rural development in the Kavango East Region administered by the Kavango East Regional Council. The Kavango East Region is the poorest region in Namibia, with an unemployment rate that is higher than the national rate. With these statistics as background, the microfinance grant was proposed as a vital tool in alleviating the poverty-stricken region and curbing the high unemployment rate. Poverty alleviation through asset accumulation and food security, financial inclusion through opening of business banking accounts, business growth and diversification were variables considered to indicate rural development. The literature indicates that microfinance has both positive and negative impacts on poor people‟s income by increasing and decreasing their incomes, respectively. Available evidence also indicates minimal proof that microfinance impacts job creation and should, therefore, not be promoted as a means to achieve long-term goals. A qualitative research methodology using the descriptive survey design was used to collect data. The analysis of the study shows that microfinance grants have not positively impacted rural development as anticipated; beneficiaries have not registered growth or diversification in their businesses. However, there has been a positive impact on financial inclusion variable as business banking accounts were opened. Overall, the positive impacts of microfinance grants are very minimal due to relatively small market sizes which reduce chances to accumulate asset from the business operations. The grants have however enabled food security as beneficiaries‟ businesses are more for subsistence than commercial purposes.